Concordance Between the TIRADS Ultrasound Scoring Criteria, Fine-Needle Aspiration Cytology, and Thyroid Final Resection Diagnosis. (11th September 2019) - Kaseb, Hatem; Charifa, Ahmad; Abi-Raad, Rita; Cai, Guoping; Hammers, Lynwood; Prasad, Manju; Adeniran, Adebowale
Abstract: Objectives: Thyroid imaging reporting and data system (TIRADS) criteria were recently introduced in our institution to aid in predicting diagnosis for various thyroid lesions. We evaluated the association of TIRADS imaging score and fine-needle aspiration (FNA) cytology with thyroid lesions that had a confirmed diagnosis at resection, with a focus on understanding the predictability of this diagnostic tool in malignancy prediction. Methods: We assessed the concordance of TIRADS criteria and FNA diagnosis to the final anatomical diagnosis in the assessment of thyroid lesions. We retrieved the cases from the archives of the Yale pathology department between June 2017 and January 2018. Our inclusion criteria included patients who had a TIRADS score, cytology diagnosis, and final surgical resection diagnosis. A total of 65 subjects with an age range of 11 to 88 years were identified. Results: The majority of the patients were females, 65% (42/65). Cases with TIRADS score 1-2 (likely benign) and Bethesda I/II nondiagnostic/benign were few since most of these cases did not go for surgical resection. The mildly suspicious TIRAD score 3 and FLUS category showed similar trends, 68% and 67%, respectively, in predicting malignant lesions. The TIRADS score 4 when compared to cytology (IV)/(V) demonstrated similar consistent results in malignancy prediction, both being high at 89% and 87%, respectively. The TIRADS score 5 demonstrated a 95% malignancy prediction. The overall sensitivity and specificity of TIRADS score in our cohort were 66% and 77%, respectively. The positive and negative predictive values of TIRADS score in our cohort were 89% and 39%, respectively. In comparison, the overall sensitivity and specificity of cytology assessment in our cohort were 91% and 44%, respectively. The positive and negative predictive values of cytology assessment in our cohort were 85% and 57%, respectively. Conclusion: Our results demonstrated that both cytology and TIRAD score had similar trends in malignancy prediction. Cytological assessment had higher sensitivity but lower specificity compared to TIRADS score. While both techniques showed concordant high predictability of malignant lesions (approximately 91%), the use of both modalities adjunctively will be very useful in triaging cases for surgery. Overall, utilizing TIRADS score with cytology will help reduce the risk of unnecessary invasive procedures in patients with a low probability of malignant thyroid disease.